UNDERSTANDING THE PUBLIC INTEREST IN DEVELOPMENT NYIA (New Yogyakarta International Airport): AN ECONOMIC ANALYSIS AND LEGAL APPROACH - Muhammad Fikri Alan (Faculty of Law, Universitas Sebelas Maret, 2019)
This paper seeks to use economic and law approaches in looking at the problems that occur over the construction of New Yogyakarta International Airport (NYIA). According to the legal approach that is often done, it has not given a clear meaning of what the phrase